2012
DOI: 10.1371/journal.pone.0038788
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Biogeography of the Slipper Orchids: Eocene Vicariance of the Conduplicate Genera in the Old and New World Tropics

Abstract: Intercontinental disjunctions between tropical regions, which harbor two-thirds of the flowering plants, have drawn great interest from biologists and biogeographers. Most previous studies on these distribution patterns focused on woody plants, and paid little attention to herbs. The Orchidaceae is one of the largest families of angiosperms, with a herbaceous habit and a high species diversity in the Tropics. Here we investigate the evolutionary and biogeographical history of the slipper orchids, which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
94
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 145 publications
18
94
1
2
Order By: Relevance
“…Separation between the two genera occurred approximately 43-41 Ma ago (Gustafsson, Verola & Antonelli, 2010) while the diversification of currently recognized species started around 21 to 10 Ma ago (Guo et al, 2012). This pattern was also observed in other flowering plants, e.g., palaeotropical genus Pseuduvaria (Annonaceae; Su & Saunders, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Separation between the two genera occurred approximately 43-41 Ma ago (Gustafsson, Verola & Antonelli, 2010) while the diversification of currently recognized species started around 21 to 10 Ma ago (Guo et al, 2012). This pattern was also observed in other flowering plants, e.g., palaeotropical genus Pseuduvaria (Annonaceae; Su & Saunders, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The value of h was slightly higher than the value of p. Due to less SNP variation, the value of h and p was similar and according to the neutrality test statistics it tends to be negative. The slipper orchids were analyzed to trace the phylogenetic relationship among the orchids species based on chloroplastic gene sequences (accD, rbcL, matK, rpoC1, rpoC2, ycf1, ycf2, and ndhF) in PAUP version 4.0b10 (Guo et al 2012).…”
Section: Analysis Of Nucleotide Diversitymentioning
confidence: 99%
“…On one hand, the broad distribution of orchids (and their great diversity) might partly reflect their excellent dispersal, conferred by the dust-like seeds of almost all species. Such disjunctions are seen within genera or pairs of closely related genera in all orchid subfamilies except Apostasioideae, suggesting that they may often have arisen early enough for continental drift to affect present-day distributions (Dressler, 1981;Chase, 2001; but see Guo et al, 2012). Dressler (1981) suggested that only 34 orchid genera had been able to cross tropical oceans and establish disjunct distributions on continents long isolated from each other (i.e.…”
Section: Introductionmentioning
confidence: 99%